BURDEN OF DECOMPENSATED LIVER DISEASE IN PAKISTAN: AN EPIDEMIOLOGICAL EVIDENCE.: JPUMHS; 2025:15: 01,229-239. http://doi.org/10.46536/jpumhs/2025/15.01.616 - Shohabudin Rind1, Mohsin Ali2, Ghulam Mustafa Jamali3, Sana Aqeel4, Naveed Sattar Shaikh5, Ali Akber Nangraj6, Mujahid Ali Chandio7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Decompensated liver disease (DLD) is a leading cause of morbidity and mortality in Pakistan, driven primarily by viral hepatitis, metabolic dysfunction-associated steatotic liver disease (MASLD), and alcohol-related liver injury. Despite its high burden, comprehensive epidemiological data remain scarce. This meta-analysis synthesizes available evidence to quantify the prevalence, etiological distribution, and clinical outcomes of DLD in Pakistan. METHODS: A systematic search was conducted across PubMed, Google Scholar, and Pakistani medical journals (2000–2023) for studies reporting DLD prevalence, etiology, complications, or mortality. Pooled estimates were calculated using random-effects meta-analysis, with subgroup analyses by etiology and region. RESULTS: Among 18 eligible studies (n=19040 patients), the pooled prevalence of DLD in cirrhotic patients was 15.6% (95% CI: 12.4–19.2%), with HCV (63.5%), HBV (18.7%), and MASLD (12.1%) as leading causes. The 1-year mortality rate was 47.3% (95% CI: 41.5–53.2%), with variceal bleeding (32%), hepatorenal syndrome (24%), and sepsis (19%) as major contributors. DLD accounted for 9.8% of hepatology admissions, with significant regional disparities higher in Punjab (17.1%) and Sindh (14.5%) compared to Khyber Pakhtunkhwa (10.3%). CONCLUSION: Pakistan faces a severe and growing burden of DLD, predominantly due to untreated viral hepatitis and rising metabolic risk factors. Delayed diagnosis, restricted access to antiviral medications, and insufficient transplant services worsen patient outcomes. Immediate public health actions, such as broadening HCV screening, providing affordable direct-acting antivirals (DAAs), and implementing strategies for preventing MASLD, are essential for alleviating this crisis.